Development Practices under Different Political Regimes in Nepal: Theoretical Explanation - Adhikari, Hemant Raj (Spectrum of Humanities and Social Sciences, 2025)
The government of Nepal has introduced and implemented many development plans, policies, and programs so far. Nepal has witnessed various development practices during different political systems. This paper is intended to review and analyse the development practices under different political regimes in Nepal. The paper employed an analytical review approach based on secondary sources to assess and analyse the development practices in Nepal. The study reveals that Nepal has implemented fifteen periodic development plans and policies; however, it still needs excellent efforts for economic progress. The People's Movement in 1990 restored Nepal's multiparty system, focusing on privatisation and financial liberalisation. The 2007 Interim Constitution introduced the concept of inclusion, and the 2015 Constituent Assembly Constitution instituted inclusion in periodic development plans. Each political regime contributed to the nation's overall development but faced difficulties contributing to its effectiveness. Nepal's development plans, programs, and policies have not fully achieved objectives, addressed rural poor issues, and lacked continuity due to unstable government and global practices.